Learning to Be a Teacher: Prospective Teachers' Experiences and Perceptions in Micro Teaching Course - Simamora, Roy Martin; Probosini, Agustina Ratri; Sarjiwo, S (Studies in Learning and Teaching, 2024)
This study aims to investigate the experiences and perceptions of prospective student teachers in microteaching courses as part of the learning process to become a teacher. The research method used was qualitative research with a case study approach. Data was collected via Google Forms to ensure maximum efficiency and internet accessibility. The data collection period started in early December 2023 and extended to early January 2024. This study examines microteaching experiences of 20 student teachers (13 females, 7 males, aged 20–24 years) from urban and rural backgrounds at the Indonesian Institute of the Arts Yogyakarta. Data were collected via questionnaires and analyzed thematically. The study used a structured questionnaire with 19 questions across 7 topics, distributed via Google Forms for efficient data collection and secure response management. The findings showed that the experiences and perceptions of pre-service teachers varied greatly, influenced by factors such as microteaching preparation; experiences during microteaching sessions; feedback and learning; perceptions and evaluations of the microteaching course; suggestions and recommendations; perceptions of the teaching career; and self-reflection. The implication of these findings is the need for a diverse approach in micro teaching to meet the needs and enrich the learning experience of pre-service teachers.